PENGARUH MOBILISASI DINI TERHADAP INTENSITAS NYERI PADA PASIEN POST OPERASI DI RSUD S.K. LERIK KUPANG TAHUN 2018 - Appolonaris Tomas Berkanis (CHMK Applied Science Journal, 2020)
ABSTRACT Background: Every individual has experienced pain in some degree. Pain is the most common reason people seek health care. Individuals who feel pain feel depressed or suffer and seek to relieve pain. Pain is subjective, no two individuals experience the same pain and no two same pain occurrences produce an identical response or feeling for an individual. Pain is a source of frustration, both the client and the health worker. Purpose: This study aimed to determine the effect of mobilization on the intensity of pain in postoperative patients. Methods: This research was a pre-experimental research with one group pre-posttest design, the data collection method used was total sampling, the research instrument used was the intensity instrument of baourbanis pain, early mobilization and mobilization instruments using observation sheets. Results: The result of hypothesis test of the effect of early mobilization on pain intensity in postoperative patient with wilcoxon test using SPSS 16 program showed that Z score = -3,947 with P-value = 0.000 then H0 is rejected and H1 received so it is concluded that there is influence of early mobilization to the intensity of pain in postoperative patients at RSUD SK Lerik Kupang. Conclusion: early mobilization affects the intensity of pain in postoperative patients so that it can be used as one of the actions of nursing in resolve pain in postoperative patient Key Words: Pain, Early Mobilization, Post Operative